MENUMBUHKAN MINAT DAN KEBUGARAN JASMANI MELALUI OLAHRAGA TRADISIONAL - Hadi Wijaya, Habibi; Basri, Hasan; Rahmasari, Tiara (Universitas Islam 45 Bekasi, 2023)
The purpose of community service activities related to fostering interest and physical fitness through traditional sports is to expand physiological, organic, motor, thinking, emotional and social development and growth as well as moral preservation of national culture. The method of implementing community service applies community education methods in the form of socialisation and traditional sports training in the form of relay and fort. Implementation of the service location in Sumbersari Village, Pebayuran District, Bekasi Regency with service partner SDN 02 Sumbersari. The results of the implementation of the service have a positive impact in the form of increasing students' thinking about collaboration, team involvement, interest in traditional sports and preservation of traditional sports culture. Thus, traditional sports training for students can be used as an effective tool in fostering interest in preserving culture and increasing students' physical fitness.